TAHLILUL MAWAD AD DIRASIYAH FI KITABI TA'LIMI AL LUGHAH AL ARABIYAH LIL JAMIAH - Siti Anisa Sholehati (UIN ANTASARI, 2018)
In learning, there is a need for teaching materials. Teaching materials are materials or materials used to assist the learning process in order to achieve the goals that have been set. Among the many teaching materials that can be used, it is usually textbooks that we often encounter for use in learning. But we also need to first analyze how the textbook is before being used in a lesson. After being analyzed, it was found that the Arabic language book for higher education used was in accordance with the principles and characteristics that had been determined.